The U.S. Air Force - Jordan, David (Milwaukee, Wis. : World Almanac Library, 2005)
This book looks at the history, strength, capabilities, deployment, and key missions of the United States Air Force, which became an independent branch of the armed forces in 1947.
Includes index.
Includes chronology.
Includes glossary.
Includes bibliography.
4-8
Accelerated Reader AR
Keywords: United States -- Air Force